Access and accessibility in web environments for persons with disabilities: progresses and boundaries - Hott, Daniela Francescutti Martins; Rodrigues, Georgete Medleg; Oliveira, Laís Pereira de (Faculdade de Filosofia e Ciências, 2018)
The democratization of access to digital data in various formats that circulate on the Internet, that is, Big Data has been a recurring theme on the world stage. In this context, discussions on accessibility for people with disabilities seem to be central and coherent with issues of access to digital information. The present study seeks to identify the regulatory frameworks for inclusion and access and accessibility restrictions in web environments for people with disabilities. The methodology used is of a qualitative nature, being the exploratory research, since it started from the studies of Information Science, Information Professional, Accessibility and the Law of Access to Information and Big Data, to establish a link between such concepts. As a result, it presents and describes the performance of the information professional in all phases of configuring a site accessible to people with disabilities. It concludes that informational accessibility in web environments depends on the mobilization around the issue of universality and equal rights guaranteed in legal apparatuses, as well as training and preparation to deal with a subject as essential as informational accessibility.